Strategy For Developing Malang City's MSMEs For The Digital Market Via B2c Marketing And Social Media Marketing - Jaladri, Chavid Moyo (KAMBOTI: Jurnal Sosial dan Humaniora, 2023)
This research aims to provide material consideration for IKM owners in particular and the Malang City Department of Cooperatives, Industry, and Trade (Diskopindag) in general. This information may be used to develop plans to increase the growth of SMEs going global. This study gathered data from searching for literature papers and distributing questionnaires. Literature review and dissemination of questionnaires to be completed by respondents Based on this idea, a sample of 400 respondents was disseminated online and offline over the internet using enumerators in this study. According to the findings of the study, SMEs utilize social media to inform and connect with their customers. The tool is really successful in informing me about IKM products and allowing me to communicate directly with customers. Furthermore, IKM forms alliances with e-commerce companies to expand digital product marketing platforms and food delivery convenience. The challenges that SMEs encounter when implementing digital marketing include inconsistent internet connections, delivery delays, and internal difficulties caused by a shortage of human resources as a result of huge orders generated by social media advertising.